Dynamics of flow transitions from bubbly to churn flow in high viscosity oils and large diameter columns. (November 2019) - Mohammed, Shara K.; Hasan, Abbas H.; Ibrahim, Abubakr; Dimitrakis, Georgios; Azzopardi, Barry J.
Highlights: Flow transitions in high viscosity liquids and large diameter columns is presented for the first time. In transition to slug, structure velocity increases at constant rate with increasing bubbles size. Taylor bubble in viscous oils appears as long cylinder, rounded top and end, no wake recirculation. Lengths of large bubbles in bubbly to slug transition, increase gradually with increasing gas flow. In slug to churn transition, liquid bridges frequency increase, creating complex flow structures. Abstract: The dynamic behaviour of the gas-liquid two phase flows and in particular the flow pattern stability and transition between the flow regimes are influenced significantly by both the properties of the liquid and gas as well as the pipe diameter. The majority of the studies reported in the literature on the dynamics of gas-liquid flow transitions focus only on low viscosity liquids (e.g. water) and small diameter pipes. In the present work a series of experiments were carried out to study the dynamics of flow transitions (bubbly to slug and slug to churn) of gas rising through very viscous oils (330 Pa s and 360 Pa s) in two large diameter columns (290 and 240 mm, respectively), using Electrical Capacitance Tomography (ECT) and pressure sensors. The experiments aimed to imitate a number of realistic flow conditions that might be encountered, for examples, in; bitumen, crude oil, viscous liquids in food processing and volcanic magmatic flows. Observation and quantification of bubbly to slug and slug to churn flow transitions for gas-high viscous liquids in large pipe diameters are presented for the first time. Flow parameters and characteristics including; void fraction, pressure gradient, Probability Density Function, structure velocity, lengths of large/Taylor bubbles and liquid slugs and the effect of liquid temperature on the void fraction and Taylor bubble lengths, were measured and analysed. It was found that transition to slug and churn flow occurs gradually. Transition to slug flow occurs at a gas superficial velocity of 0.011 m/s–0.016 m/s, while transition to churn appears in the range of 0.127–0.243 m/s in both columns.